PERFORMANCE OF BALI BULL IN GREENLOT FATTENING BY FARMERS WHEN RAINY SEASON IN TIMOR ISLAND - Tahuk, P.K.; Dethan, A.A. (Diponegoro University, 2010)
The objective of this research was to determine the performance of Bali bull in rainy season underfeedlotting management on farmer level in Timor Island. Twenty Bali bulls with 2.0-2.5 years old on thebasis of teeth eruption were used in this study. Feed for animals was field grass, king grass and cornstraw. The type, quantity and quality of feed given in accordance with the habits of farmers in thefattened cattle. Research was conducted by direct observation in farmer management during rainyseason. Data measured were daily gain, feed consumption and feed conversion. The data collected wastabulated and analyzed descriptively. The result showed that the average of daily gain weight was 0.53kg/head/d, dry matter intake was 3.88 kg/head/d and feed conversion was 7.55 kg DM/kg daily gain. Inconclusion, performance of Bali bull fattened at farmers level with forage in the rainy season could beimproved.